Economic and environmental evaluation of emerging electric vehicle technologies - Horesh, Noah, author; Quinn, Jason, advisor; Bradley, Thomas, committee member; Jathar, Shantanu, committee member; Willson, Bryan, committee member (Colorado State University. Libraries, 2023)
As the transportation sector seeks to reduce costs and greenhouse gas (GHG) emissions, electric vehicles (EVs) have emerged as a promising solution. The continuous growth of the EV market necessitates the development of technologies that facilitate an economically comparable transition away from internal combustion engine vehicles (ICEVs). Moreover, it is essential to incorporate sustainability considerations across the entire value chain of EVs to ensure a sustainable future. The sustainability of EVs extends beyond their usage and includes factors such as battery production, charging infrastructure, and end-of-life management. Techno-economic analysis (TEA) and life cycle assessment (LCA) are key methodologies used to evaluate the economic and environmental components of sustainability, respectively. This dissertation work uses technological performance modeling combined with TEA and LCA methods to identify optimal deployment strategies for EV technologies. A major challenge with the electrification of transportation is the end of life of battery systems. A TEA is utilized to assess the economic viability of a novel Heterogeneous Unifying Battery (HUB) reconditioning system, which improves the performance of retired EV batteries before their 2nd life integration into grid energy storage systems (ESS). The modeling work incorporates the costs involved in the reconditioning process to determine the resale price of the batteries. Furthermore, the economic analysis is expanded to evaluate the use of HUB reconditioned batteries in a grid ESS, comparing it with an ESS assembled with new Lithium-ion (Li-ion) batteries. The minimum required revenue from each ESS is determined and compared with the estimated revenue of various grid applications to assess the market size. The findings reveal that the economical market capacity of these applications can fully meet the current supply of 2nd life EV batteries from early adopters in the United States (U.S.). However, as EV adoption expands beyond early adopters, the ESS market capacity may become saturated with the increased availability of 2nd life batteries. Despite the growing interest in EVs, their widespread adoption has been hindered, in part, by the lack of access to nearby charging infrastructure. This issue is particularly prevalent in Multi-Unit Dwellings (MUDs) where the installation of chargers can be unaffordable or unattainable for residents. To address this, TEA methodology is used to evaluate the levelized cost of charging (LCOC) for Battery Electric Vehicles (BEVs) at MUD charging hubs, aiming to identify economically viable charger deployment pathways. Specifically, multiple combinations of plug-in charger types and hub ownership models are investigated. Furthermore, the total cost of ownership (TCO) is assessed, encompassing vehicle depreciation, maintenance and repair, insurance, license and registration, and LCOC. The study also conducts a cradle to grave (C2G) LCA comparing an average passenger BEV and a gasoline conventional vehicle (CV) using geographical and temporal resolution for BEV charging. The TCO is coupled with the C2G GHG emissions to calculate the cost of GHG emissions reduction. The analysis demonstrates that MUD BEVs can reduce both costs and GHG emissions without subsidies, resulting in negative costs of GHG emissions reduction for most scenarios. However, charging at MUDs is shown to be more expensive compared to single-family homes, potentially leading to financial inequities. Additional research is required to assess the advantages of public charging systems and commercial EVs. While home charging is typically the primary option for EVs, public charging infrastructure is necessary for long-distance travel and urgent charging. This is especially important for commercial vehicles, which rely on public charging to support their operational requirements. Various charging systems have been proposed, including Direct Current Fast Charging (DCFC), Battery Swapping (BSS), and Dynamic Wireless Power Transfer (DWPT). This work includes a comparison of the TCO and global warming potential (GWP) of EVs of various sizes, specifically examining the charging systems utilized to determine precise location-specific sustainability outcomes. Nationwide infrastructure deployment simulations are conducted based on the forecasted geospatial and temporal demand for EV charging from 2031 to 2050. The TEA and LCA incorporate local fuel prices, electricity prices, electricity mixes, and traffic volumes. To account for the adaptability of variables that highly influence TCO and GWP, optimistic, baseline, and conservative scenarios are modeled for EV adoption, electricity mixes, capital costs, electricity prices, and fuel prices. The change to TCO by switching from ICEVs to EVs is shown to vary across scenarios, vehicle categories, and locations, with local parameters dramatically impacting results. Further, the EV GWP depends on local electricity mixes and infrastructure utilizations. This research highlights the dynamic nature of EV benefits and the potential for optimal outcomes through the deployment of multiple charging technologies. In conclusion, this research underscores the significance of strategically deploying EV charging infrastructure and utilizing retired EV batteries for grid energy storage. Instead of posing a challenge at end of life, these batteries are shown to be a solution for grid energy storage. The study also highlights the economic advantages of different charging infrastructure types for EVs and their role in driving EV adoption, resulting in potential GHG emissions reductions and consumer savings. Ultimately, widespread EV adoption and decarbonization of electrical grids are pivotal in achieving climate goals.